2019
DOI: 10.1111/jvim.15689
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of phosphorus, calcium, and magnesium content in commercially available foods formulated for healthy cats

Abstract: Background: High dietary phosphorus (P) and low calcium-to-phosphorus ratio (Ca:P) are associated with kidney damage in cats. There are no established guidelines for dietary P maximum for cats.Objectives: To quantify crude protein, P, Ca, and magnesium (Mg) concentrations in cat foods and compare among food formats (dry, canned, raw), primary protein ingredients, protein concentrations (low, moderate, high), grain-free versus grain-containing foods, foods intended for adult maintenance versus all life stages, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Two diets were tested at this level, containing either 4g/1000kcal (4184kJ) or 5g/1000kcal (4184kJ) levels of total P, with Ca:P ratios of 1 and 1.3, respectively. Our aim was to not only investigate the effect of this level of STPP inclusion, but also any potential interactions with higher total P levels observed among commercial dry diets (11) . This enabled two hypotheses to be tested, firstly that a diet formulated to 4g/1000kcal (4184kJ) total P (incorporating 1g P from STPP) and a Ca:P =1 would not cause observable adverse effects; and secondly increasing the total P to 5g/1000kcal (4184kJ), while maintaining STPP contribution at 1g, with a Ca:P of 1.3 would also not cause observable adverse effects and allow more flexibility in dietary formulations using organic raw materials.…”
Section: Introductionmentioning
confidence: 99%
“…Two diets were tested at this level, containing either 4g/1000kcal (4184kJ) or 5g/1000kcal (4184kJ) levels of total P, with Ca:P ratios of 1 and 1.3, respectively. Our aim was to not only investigate the effect of this level of STPP inclusion, but also any potential interactions with higher total P levels observed among commercial dry diets (11) . This enabled two hypotheses to be tested, firstly that a diet formulated to 4g/1000kcal (4184kJ) total P (incorporating 1g P from STPP) and a Ca:P =1 would not cause observable adverse effects; and secondly increasing the total P to 5g/1000kcal (4184kJ), while maintaining STPP contribution at 1g, with a Ca:P of 1.3 would also not cause observable adverse effects and allow more flexibility in dietary formulations using organic raw materials.…”
Section: Introductionmentioning
confidence: 99%
“…15 One-third of the foods for senior cats had phosphorus concentrations ≥3.6 g/1000 kcal ME, similar to the proportion of foods for adult cats exceeding this concentration in a previously reported nutritional analysis of 81 foods. 9 This value is of concern considering that a previous study found an association between high phosphorus intake in cats with CKD before diagnosis compared to a group of control cats, 18 and foods with excessive inorganic phosphorus (>3.6 g/1000 kcal ME of total phosphrus, with ≥1.5 g/1000 kcal ME as inorganic phosphorus) have been shown to promote ultrasonographic renal changes and renolith formation in healthy cats. 19,20 is a rough assessment of insoluble fiber only and does not represent the total content of fiber in the food.…”
Section: Discussionmentioning
confidence: 99%
“…Values from a subset of adult cat foods (1 lot number per food; n = 59) described in a previous publication were used for comparison. 9…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Excess phosphorus may cause sustained kidney damage and decreased renal function in some cats (Summers et al . 2020) and limiting dietary phosphorus in cats with chronic kidney disease (CKD) appears to help delay CKD progression (Geddes et al . 2016, Liera 2020).…”
Section: Additives Associated With Safety Issues In People and Animal Species Other Than Dogs And Catsmentioning
confidence: 99%